2016
DOI: 10.15826/chimtech.2016.3.2.008
|View full text |Cite
|
Sign up to set email alerts
|

Extractants for rare earth metals

Abstract: The separation of trivalent rare earth metals is perhaps the most serious challenge associated with a closed fuel cycle. The choice of ligand as extractant, which must be selective and efficient in conditions of high radiation environment, plays an important role. In this review there are the main examples of extractants for f-elements used in the present 10-20 years. Экстрагенты для редкоземельных металловРазделение трехвалентных редкоземельных металлов, возможно, является самым се-рьезным вызовом, связанным… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It can be shown that making use of the Eqs. (1)(2)(3)(4)(5), this is equivalent to the formula: where: ′ LnL3 is bed distribution coefficient of the complex ion.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be shown that making use of the Eqs. (1)(2)(3)(4)(5), this is equivalent to the formula: where: ′ LnL3 is bed distribution coefficient of the complex ion.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…In the last decades, the problem of recovery of precious and rare metals from various forms of electronic wastes gained considerable attention and has been discussed in several papers and reviews [14][15][16]. Preliminary separation of REE from other elements is usually achieved by solvent extraction and/ or ion exchange [3][4][5].…”
Section: Possible Uses Of the New Chromatographic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Their high selectivity can be achieved by changing the glycol chain numbers and introducing substituents to their structure. Such operations limit the availability of crown ethers as extractants for REE on a commercial scale [16]. Besides, there is data about their poor effectiveness in acidic solutions with low pH values [17].…”
Section: Selection Of the Extractantmentioning
confidence: 99%